Associations between obesity parameters and the risk of incident atrial fibrillation and ischaemic stroke in the different age groups - Ahn, Hyo-Jeong; Lee, So-Ryoung; Choi, Eue-Keun; Han, Kyung-Do; Rhee, Tae-Min; Kwon, Soonil; Kim, Sunwha; Oh, Seil; Lip, Gregory Y. H. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Obesity and ageing are important predisposing factors to atrial fibrillation (AF) and ischaemic stroke (IS). However, limited data comprehensively evaluated the relationships between obesity measurements and AF and IS in the different ages. Methods: 9,432,332 adults from the Korean National Health Insurance Service database were included. The study population was categorised into six age subgroups by an increase in every decade from the twenties. We evaluated AF and IS risk according to body mass index (BMI) and waist circumference (WC) in different age groups. Results: During a mean follow-up of 8.2±1.0 years, BMI-AF presented a J-shaped association across age. The highest hazard ratio (HR) of BMI≥30kg/m2 group was observed in subjects aged 30–39 years [HR 1.80, 95% confidence interval (CI) 1.63-1.98, p<0.001]. Underweight adults over 60 years also presented an increased AF risk. Incident IS risk increased in those with BMI over the normal range in early and midlife, but the association became obscured in adults aged>60 years. Among BMI≥30kg/m2 groups, subjects aged 20–29 years presented the highest risk of IS [HR 3.00, 95% CI (2.34-3.84), p<0.001]. Overall, WC-AF and WC-IS showed positive linear correlations, but WC-IS association was weak in subjects aged≥40 years. Conclusions: The higher risks of AF and IS according to an increment of BMI and WC were most apparent among the young ages. The association between obesity measurements and IS was not significant above the midlife. Weight management in the young and an integrated risk factor management in the elderly is warranted.